«If you don't Expose Children, they are not Going to get Interested» Temple Grandin interview - T. Grandin; S.M. Edelson (Moscow State University of Psychology and Education, 2020)
Present interview of Temple Grandin, PhD in animal science, professor of Colorado State University, given to guest editor of the Journal Stephen Edelson discusses person's with autism perception of changes in lifestyle associated with the onset of the COVID-19 pandemic. During the interview, Professor Grandin gives advice on the schooling of children with ASD during the transition to distance learning. The questions of employment of people with autism are also proposed - what positions are best for people with ASD, how to get the employer interested in hiring a person with autism.